Functional materials synthesis via pulse electrolysis mode - Sakhnenko, M. D.; Zhelavska, Yu. A.; Rudneva, S. I.; Proskurina, V. O.; Pospielov, O. P. (CPN Publishing Group, 2024)
Cobalt-vanadium alloy coating was electrodeposited from complex citrate electrolyte via pulse electrolysis modes. The resulting coating contains 0,2-1,45 % vanadium. Based on research results, electrodes with cobalt-vanadium coating have electrocatalytic activity for HER and can be recommended as energy-saving cathode material for the electrochemical production of hydrogen.
Keywords: electrocatalytic activity; Co-V coating; overpotential; pulse electrolysis modes